Clinical Characteristics, Antifungal Susceptibility, and Prognosis of Candidozyma auris Infections: A Single-Center Retrospective Study - Esra Kazak; Emel Yilmaz; Zilan Konak; Büşra Çalışır; Uğur Önal; Melek Öztürk Demir; Esma Souleiman; Hafize Aysun Yılmaz; Habibe İmer; Hatice Aydın Tüfekçi; Gül Çalışkan; Laman Aliyeva; et al. (Uludağ Üniversitesi Tıp Fakültesi Dergisi, 2026)
Candidozyma auris (formerly Candida auris) is an emerging multidrug-resistant fungal pathogen associated with healthcare-associated infections and high mortality. This study evaluated the clinical characteristics, antifungal susceptibility profiles, and risk factors for candidemia and mortality in patients with C. auris isolation. This retrospective cohort study included patients with at least one clinical specimen positive for C. auris between May 2023 and June 2025. Patients were classified as having colonization or infection based on clinical and microbiological criteria. Trend analysis evaluated changes across colonization, non-bloodstream infection, and candidemia, and risk factors for candidemia and mortality were assessed using Firth penalized logistic regression. Forty-nine patients were included (median age, 67 years), of whom 63.3% were in the intensive care unit at the time of isolation. Colonization and infection were identified in 55.1% and 44.9% of patients, respectively, with candidemia being the most common presentation (68.2% of infections). The frequencies of intensive care unit stay, central venous catheter use, and total parenteral nutrition increased significantly from colonization to candidemia (p for trend <0.05). In multivariable analysis, intensive care unit stay (aOR 4.2, p=0.03) and total parenteral nutrition (aOR 6.9, p=0.04) were independently associated with candidemia. All isolates were resistant to fluconazole, echinocandins showed high in vitro activity, and amphotericin B MICs were ≥2 μg/mL in 64.3% of isolates. Overall, in-hospital mortality was 46.9%. Charlson Comorbidity Index, total parenteral nutrition, and clinically significant infection were independently associated with in-hospital mortality.